Laplace in Mechanical Systems

Using Laplace transforms to solve mechanical ordinary differential equations.\(\)


Before we look at examples of mechanical systems, let’s recall the equations of mechanical element.


According to Hooke’s law, the reactive force is linear proportional to the displacement and opposite the direction of the force

own work

$$f_s(t)=S\cdot x(t)\label{eq:spring}\tag{1}$$

where \(S\) is the spring stiffness [N/m].


A dashpot provides friction force linear proportional with the velocity and opposite the direction of the force.

own work

$$f_r(t)=R\cdot \frac{\mathrm{d}x(t)}{\mathrm{d}t}\label{eq:damper}\tag{2}$$

where \(R\) is the resistance, or damping coefficient [Ns/m]


According to Newton’s second law of motion the reactive force is linear proportional to the acceleration and opposite the direction of the force

own work

$$f_m(t)=M\cdot \frac{\mathrm{d}^2x(t)}{\mathrm{d}t^2}\label{eq:mass}\tag{3}$$

where \(M\) is the mass [kg]


First Order Example

Constant force on horizontal parallel damper and spring, starting at \(t=0\)

own work$$f_{e}(t)=F_0\gamma(t)\label{eq:applied}\tag{4}$$

Sum of the forces must be zero.  This combine the equations for the external force \(\eqref{eq:applied}\) with the equations for spring \(\eqref{eq:spring}\) and damper \(\eqref{eq:damper}\).

f_r(t) + f_s(t)&=f_e(t) \\
R\frac{\mathrm{d}x(t)}{\mathrm{d}t} + S x(t) &= F_0\gamma(t)

Transform this to the ordinary differential equation, knowing that the system starts from rest, therefor \(\frac{\mathrm{d}x(0)}{\mathrm{d}t}=0\) and \(x(0)=0\).

$$R\,s\,X(s)+ S X(s)=F_0\frac{1}{s}$$

Solve for \(X(s)\)

X(s) (s R +S)&=F_0\frac{1}{s} \\
\Rightarrow\ X(s)&=\frac{F_0}{s(s R +S)}

To return back to the time domain \(x(t)\), we need to find a reverse Laplace transform.  There is none.  According to Heaviside, this can be expressed as partial fractions.  [swarthmore]


The constants \(c_{0,1}\) are found using Heaviside’s Cover-up Method [swarthmoreMIT-cu]:  multiply \(\eqref{eq:heaviside}\) with respectively \(s\)  and \((sR-S)\).


Given that these equations are true for any value of \(s\), choose two convenient values to find \(c_0\) and \(c_1\)


The unit step response \(x(t)\) follows from the inverse Laplace transform of \(\eqref{eq:heaviside}\)

x(t)&= \mathcal{L}^{-1}\left\{\frac{c_0}{s}\right\}+\mathcal{L}^{-1}\left\{\frac{c_1}{sR+S}\right\} & t\geq0\\
&= \mathcal{L}^{-1}\left\{\frac{c_0}{s}\right\}+\frac{1}{R}\mathcal{L}^{-1}\left\{\frac{c_1}{s+\frac{S}{R}}\right\} & t\geq0\\
&=c_0+\frac{1}{R}c_1e^{-\frac{S}{R}t} & t\geq0

Substituting the constants \(\eqref{eq:constants1}\) gives the unit step response

x(t)&=\frac{1}{S}F_0+\frac{1}{\cancel{R}}(-\frac{\cancel{R}}{S}F_0)e^{-\frac{S}{R}t} & t\geq0\\
&=\frac{1}{S}F_0\left(1-e^{-\frac{S}{R}t}\right) & t\geq0\\


Coert Vonk

Coert Vonk

Independent Firmware Engineer at Los Altos, CA
Welcome to the things that I couldn’t find.This blog shares some of the notes that I took while deep diving into various fields.Many such endeavors were triggered by curious inquiries from students. Even though the notes often cover a broader area, the key goal is to help the them adopt, flourish and inspire them to invent new technology.
Coert Vonk

Latest posts by Coert Vonk (see all)

Leave a Reply

You can use these HTML tags

<a href="" title=""> <abbr title=""> <acronym title=""> <b> <blockquote cite=""> <cite> <code> <del datetime=""> <em> <i> <q cite=""> <s> <strike> <strong>




Protected with IP Blacklist CloudIP Blacklist Cloud